Changes in soil organic matter and phosphorus fractions under planted fallows and a crop rotation system on a Colombian volcanic-ash soil - Phiri, S; Barrios, E.; Rao, Idupulapati M.; Singh, B.R. (Springer, 2001)
Planted tree or shrub fallows can help increase the fertility of degraded tropical soils. We investigated the effects of planted fallows of Indigofera (IND), Calliandra (CAL), and Tithonia (TTH); a natural, unmanaged fallow (NAT); and a maize/bean rotation (ROT) on the dynamics and partitioning of soil organic matter (SOM) and phosphorus (P). One year after treatment, samples were collected from a fine-textured volcanic-ash soil (Oxic Dystropept) of a mid-altitude hillside in southwestern Colombia. The SOM in the sand-size fraction (150–2000 ?m) was subdivided into light (LL), intermediate (LM), and heavy (LH) fractions. Total soil P was also fractionated into inorganic (Pi) and organic (Po). Of the planted fallows, TTH most increased and NAT least increased plant-available Pi and Po. The amounts of C, N, and P in the LL and LM fractions of SOM followed the order, TTH>CAL>NAT>ROT>IND and CAL>TTH>IND>NAT>ROT, respectively. Total amounts of N, P, K, Ca, and Mg in the soil were significantly (P < 0.05) highest under TTH and lowest under NAT. The fallow and ROT systems did not affect the C/N, C/P, and N/P ratios in the soil but significantly did so in the LL and LM fractions of SOM. Significant correlations indicated that the P content in the LL and LM fractions of SOM may help determine the amounts of NaHCO3-extractable Pi and Po, which may therefore serve as sensitive indicators of `readily available' and `readily mineralizable' soil P pools, respectively, in the volcanic-ash soils of the Andes.